AN OVERVIEW OF STUDENT’S ANXIETY IN ASSALAFIYAH II MLANGI BOARDING SCHOOL YOGYAKARTA BASED ON AGE AND GENDER - Fajrul Falah Farhany; Meyka Budi Rachmawati; Winda Ernia; Natasya Putri Imam Rahmawati; Naily Zahrotun Arifah (Indonesian Journal of Community Health Nursing, 2023)
Introduction: Anxiety is a feeling of fear that is unclear and not supported by the situation. When anxious, the individual feels discomfort or fear with no identifiable object. Anxiety disorders are one of the most common psychological disorders in adolescent patients. Every individual is inseparable from anxiety. The anxiety can be mild, moderate, or severe. At school, students also experience anxiety for various reasons, such as anxiety about subjects, anxiety about failing in learning, and others. Method: This quantitative descriptive study was conducted at the Assalafiyah II Mlangi Islamic Boarding School in July-September 2022. The target population in this study included 840 students using a total sampling technique. Data was collected online with Generalized Anxiety Disorder (GAD) questionnaires. Result: The results showed significant differences in the level of anxiety based on aged in Assalafiyah II Mlangi Islamic Boarding School (p-value 0.026) and significant results at the level of anxiety based on gender (p-value 0.000). Conclusion: Female students need more anxiety counseling than male students. Besides that, there was no relationship between age and anxiety. This study assists in developing a strategic plan to reduce anxiety among boarding school students by developing Counseling Guidance Teachers or Psychologists. Keywords: Mental Health, Anxiety, Islamic Boarding School, Students.